2019
DOI: 10.1049/iet-rpg.2019.0339
|View full text |Cite
|
Sign up to set email alerts
|

Methods to aggregate turbine and network impedance for wind farm resonance analysis

Abstract: Small-signal sequence impedance models have been developed for different types of wind turbines and used in industry to study wind farm and high-voltage direct current (HVDC) system harmonics and resonances. Compared to other small-signal methods, a major advantage of system modelling and analysis based on sequence impedance is its scalability: an equivalent impedance model can be easily built for any complex system by aggregating the impedance of individual turbines and the network. A recent development in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Moreover, [145] showed that the outer control loop and PLL are two main factors producing asymmetry in the impedance modeling. The impedance modeling of the DFIG system taking the sequence coupling into consideration is discussed in [144,146]. Reference [147] has discussed the frequency coupling effect on the SSR and HFR in the DFIG system.…”
Section: Impedance-based Model Analysismentioning
confidence: 99%
“…Moreover, [145] showed that the outer control loop and PLL are two main factors producing asymmetry in the impedance modeling. The impedance modeling of the DFIG system taking the sequence coupling into consideration is discussed in [144,146]. Reference [147] has discussed the frequency coupling effect on the SSR and HFR in the DFIG system.…”
Section: Impedance-based Model Analysismentioning
confidence: 99%
“…Since this additional impedance depends on the location of the turbine, it has to be modeled differently for each turbine. A systematic method to develop an aggregated farm model that takes into account these factors was introduced in [29]. For easy reference, the method is summarized here using the notations introduced in this work.…”
Section: B Farm Impedance Modeling By Aggregationmentioning
confidence: 99%
“…As the case study in [29] demonstrated, coupling through the grid and collection network impedance is important to consider in farm-grid system stability analysis when the grid is weak and/or the concern is low-frequency instability caused by PLL and dc bus voltage control. The general method to develop an aggregated farm model for this purpose presented here can also be applied to PV and other systems that involve multiple converters operating in close proximity.…”
Section: B Farm Impedance Modeling By Aggregationmentioning
confidence: 99%
“…Ref. [17] generalized (54) in a matrix form for modeling of wind and PV farms to include the effects of the impedance of both the distribution network inside the farm and the transmission line connecting to the farm. Since the characteristics of the aggregated farm impedance are similar to that of individual turbines, we will use the simpler model (54) in the following by considering a single turbine and scaling up the grid impedance to represent the condition for a wind farm.…”
Section: B Turbine-grid System Stabilitymentioning
confidence: 99%